2019
DOI: 10.3389/fpsyg.2018.02792
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical-Psychological Perspective on Somatization Among Immigrants: A Systematic Review

Abstract: Background: Somatic and psychopathological conditions (e.g., anxiety, depression, post-traumatic stress disorder, and somatization) are frequent among immigrants belonging to various ethnic groups. Worldwide findings on the epidemiology regarding specific mental conditions still vary with respect to different migration samples and migration contexts. This inconsistency also holds true in the incidence of somatization among migrants. We carried out a systematic review analyzing the relationship between migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 80 publications
2
46
0
Order By: Relevance
“…These ndings suggest that somatization may be an important aspect of trauma, one of the greatest causes of emotional distress (28). Evidence con rming this assumption was found in several refugee samples, for example in 128 Somali refugees in Finland or 1147 traumatized refugees in the Netherlands reporting a positive correlation between somatization and the number of previous traumatic events (22,29,30).…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…These ndings suggest that somatization may be an important aspect of trauma, one of the greatest causes of emotional distress (28). Evidence con rming this assumption was found in several refugee samples, for example in 128 Somali refugees in Finland or 1147 traumatized refugees in the Netherlands reporting a positive correlation between somatization and the number of previous traumatic events (22,29,30).…”
mentioning
confidence: 80%
“…It was striking that the in uence of post-migratory general psychosocial stress on SOD was greater than that of traumatic experiences. All predictors have already been found in different samples of refugees and host countries except for the concept of general psychosocial stress (14,17,22,31). Instead, however, parts of this construct, such as bad economic status, have already been identi ed as risk factors for SOD (31,46).…”
Section: Risk Factors For Increased Somatic Distressmentioning
confidence: 99%
“…Haller, Cramer, Lauche, and Dobos (2015) indicated somatization, including post-traumatic stress disorder (PTSD), in diverse ethnic immigrant groups growing all over the world. The systematic review and a meta-analytical study done by Lanzara, Scipioni, and Conti (2019) reviewing 42 papers published between 2000 and 2017 with 38 cross-sectional analyses disclosed the prevalence and correlates of somatization (including PTSD) across the immigrant groups, depending on cultural variation, in reasons for migration, stress exposure, explanatory models of illness, coping, and other individual variables.…”
Section: Post-traumatic Stress Disordermentioning
confidence: 99%
“…We presuppose trauma exposure is common throughout the whole world, unequally distributed, and differential across trauma types concerning PTSD risk (Kessler et al, 2017). In the meta-analytical study of 42 research papers, in only four of them was somatization found to be significantly prevalent in immigrants relative to the country's natives (Lanzara et al, 2019). Referring to Turkish population, only a few studies proved psychosomatic prevalence versus the locals.…”
Section: Post-traumatic Stress Disordermentioning
confidence: 99%
“…A recent systematic review argues that immigrants with somatization disorders perceive a greater need for the use of health services and greater di culties in their daily lives than those who do not have them. However, there are differences in the prevalence of somatization disorders between different groups of immigrants, depending on culture, exposure to stress, explanatory models of the disease, coping and other individual variables (12).…”
Section: Introductionmentioning
confidence: 99%